2014
DOI: 10.1155/2014/160421
|View full text |Cite
|
Sign up to set email alerts
|

Rituximab Induced Interstitial Lung Disease in Patients with Non-Hodgkin’s Lymphoma: A Clinical Study of Six Cases and Review of the Literature

Abstract: Background.Rituximab-induced lung disease (R-ILD) is a rare entity that should be considered in patients treated with rituximab who present with dyspnea, fever, and cough but no clear evidence of infection.Aim.The aim of this prospective longitudinal study is to describe the clinical presentation, management, and response to rechallenge in patients diagnosed with rituximab induced ILD over a period of one year.Results.Out of sixteen patients with CD20 positive non-Hodgkin’s lymphoma who received rituximab alon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 19 publications
0
6
0
2
Order By: Relevance
“…The onset of pulmonary complications after the third or fourth dose of rituximab as happened in our case is not unusual and has been described by Liote et al In the largest case series of 45 patients [ 2 ]. Krishnaswamy et al also reported six patients of rituximab-induced ILD in patients of non-Hodgkin lymphoma whereby the median time of presentation was usually after the third dose and the presenting symptoms were acute onset of fever, cough, and SOB or its combinations [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The onset of pulmonary complications after the third or fourth dose of rituximab as happened in our case is not unusual and has been described by Liote et al In the largest case series of 45 patients [ 2 ]. Krishnaswamy et al also reported six patients of rituximab-induced ILD in patients of non-Hodgkin lymphoma whereby the median time of presentation was usually after the third dose and the presenting symptoms were acute onset of fever, cough, and SOB or its combinations [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Treatment of rituximab-induced ILD is supplement oxygen, methylprednisolone, and supportive ventilation [ 5 , 6 ]. The dosage and duration of steroids are not yet standardized as the cases encountered are quite rare.…”
Section: Discussionmentioning
confidence: 99%
“…Rare respiratory side effects, mostly described in recent literature include transient respiratory symptoms as part of an infusion-related reaction, hypersensitivity pneumonitis, interstitial pneumonitis, organizing pneumonia, pulmonary fibrosis, and alveolar hemorrhage. [ 5 ]…”
Section: Discussionmentioning
confidence: 99%
“…Lung examination revealed diffuse bilateral scattered inspiratory crackles, tachycardia, tachypnea, and hypoxemia requiring 3 L of oxygen. Laboratory test showed a white blood cell count of 5900/mm 3 A positron emission tomography (PET-SCAN) is requested as part of unexplained hypercalcemia to exclude a malignant tumor and bone metastases and sarcoidosis but did not reveal any malign lesion and ruled out any extra-pulmonary pathological suspicious abnormalities (Figure 4).…”
Section: Case Twomentioning
confidence: 99%
“…Details of RTX-ILD have been described in a systematic review [3], and the most common symptoms are dry cough, exertional dyspnea, and fever. Nonspecific symptoms are less common and included fatigue, rigors, wheeze, hemoptysis, skin rash, and pleuritic chest pain.…”
Section: Clinical Settings Timing and Images Characteristicsmentioning
confidence: 99%